Sprayable, Large‐Area Metal–Organic Framework Films and Membranes of Varying Thickness. Issue 10 (20th January 2017) - Hurrle, Silvana; Friebe, Sebastian; Wohlgemuth, Jonas; Wöll, Christof; Caro, Jürgen; Heinke, Lars
Abstract: Despite their huge potential for efficient molecular separation, the fabrication of membranes from metal–organic frameworks (MOFs) remains a major challenge. The powders obtained by the conventional solvothermal MOF syntheses are difficult to process, and as a result the fabrication of well‐performing, large‐area MOF‐based membranes is still awaiting success. The deposition of MOF thin films suited for membrane applications is demonstrated by employing a step‐by‐step spray method. This method can be scaled up to obtain industrially relevant membrane areas and a continuous process is also possible. The performance of sprayed HKUST‐1‐based membranes by the separation of a binary H2 /CO2 mixture is also demonstrated. Furthermore, this approach enables the control of the MOF film thickness, and thus controlling the permeance and the selectivity of the membrane. Abstract : Metal–organic framework (MOF) thin films and MOF membranes were prepared with a step‐by‐step spray method. Membrane performance was demonstrated by separation of a H2 /CO2 mixture with HKUST‐1 MOF membranes. Apart from controlling MOF film thickness, and thus the membrane permeance and selectivity, this approach enables a straightforward scale‐up to large, industrially relevant membrane areas.